2022
DOI: 10.3389/fonc.2022.1009881
|View full text |Cite
|
Sign up to set email alerts
|

N6-methylandenosine-related immune genes correlate with prognosis and immune landscapes in gastric cancer

Abstract: ObjectivesThis study aimed to probe into the significance of N6-methyladenosine (m6A)-related immune genes (m6AIGs) in predicting prognoses and immune landscapes of patients with gastric cancer (GC).MethodsThe clinical data and transcriptomic matrix of GC patients were acquired from The Cancer Genome Atlas database. The clinically meaningful m6AIGs were acquired by univariate Cox regression analysis. GC patients were stratified into different clusters via consensus clustering analysis and different risk subgro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 70 publications
0
2
0
Order By: Relevance
“…22,23 Indeed, both expression levels of m6A and m6A mediators are dysregulated in numerous cancers, which are extensively linked with drug resistance. 24 An increasing number of studies have demonstrated the suppressive action of ALKBH5 on the growth of a plethora of cancer cells, including pancreatic cancer 25 and bladder cancer. 26 Of note, the hard-done work of our peers has brought to light that tumor tissues from lung adenocarcinoma patients present low expression levels of ALKBH5 and ALKBH5 downregulation is indicative of a poorer overall survival, 27 which is in consistency with the bioinformatics analysis results in our study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…22,23 Indeed, both expression levels of m6A and m6A mediators are dysregulated in numerous cancers, which are extensively linked with drug resistance. 24 An increasing number of studies have demonstrated the suppressive action of ALKBH5 on the growth of a plethora of cancer cells, including pancreatic cancer 25 and bladder cancer. 26 Of note, the hard-done work of our peers has brought to light that tumor tissues from lung adenocarcinoma patients present low expression levels of ALKBH5 and ALKBH5 downregulation is indicative of a poorer overall survival, 27 which is in consistency with the bioinformatics analysis results in our study.…”
Section: Discussionmentioning
confidence: 99%
“…m6A is broadly regarded as the most predominant and abundant internal transcript modification in eukaryotic mRNA and possesses essential roles in cancer progression, and ALKBH5 is flagged as an m6A demethylase that responsible for eliminating m6A modification from RNAs and contributing to the maintenance of a dynamic equilibrium 22,23 . Indeed, both expression levels of m6A and m6A mediators are dysregulated in numerous cancers, which are extensively linked with drug resistance 24 . An increasing number of studies have demonstrated the suppressive action of ALKBH5 on the growth of a plethora of cancer cells, including pancreatic cancer 25 and bladder cancer 26 .…”
Section: Discussionmentioning
confidence: 99%